Effect of Pesticides on Biological Control Potential of Neoscona theisi (Araneae: Araneidae). Issue 2 (27th March 2019) - Tahir, Hafiz Muhammad; Basheer, Tayyba; Ali, Shaukat; Yaqoob, Rabia; Naseem, Sajida; Khan, Shafaat Yar
Abstract: The present study was designed to record the effect of λ-cyhalothrin, Bifenthrin, and Glyphosate on the mortality, avoidance behavior, foraging activity, and activity of Acetylcholine esterase (AChE) and Carboxylesterase (CarE) in Neoscona theisi (Walckenaer, 1841). Highest mortality (70%) in N. theisi was recorded against λ-cyhalothrin. However, Glyphosate was found to be least toxic. Spider spent less time on insecticides/herbicide-treated surfaces. Insecticides/herbicide-treated N. theisi consumed less prey than untreated control spiders. Similarly, when N. theisi were offered insecticide/herbicide-treated prey, they consumed significantly less. Increased AChE and CarE activities were recorded in insecticides/herbicide-treated spiders as compared to control group. Total protein contents were less in insecticides/herbicide-treated spiders than control group. The results revealed that λ-cyhalothrin is more harmful to spiders as compared to Bifenthrin and Glyphosate. It is suggested that the effect of all pesticides used in agro-ecosystem on beneficial insects should be evaluated before using them in the fields.